Advances in Viroporin Function and Structure: A Comparative Analysis of Alphavirus 6K with Well-Characterized Viroporins - Vashi Negi; Andrew S. Miller; Richard J. Kuhn (Viruses, 2025)
Viruses encode ion channel proteins called viroporins to assist in infection and immune evasion. The alphavirus 6K protein is classified as a member of the viroporin family of proteins. Several studies have characterized the role of 6K in alphavirus budding and infection since its discovery in the late 1970s. In this review, we summarize 6K research and discuss some unanswered questions regarding 6K biology. We highlight the similarities and differences between 6K and viroporins of clinically relevant viruses—influenza A virus, HIV-1, hepatitis C virus, and SARS-CoV-2—and address their importance as therapeutic targets. The sensitivity of these viroporins to common inhibitors and their ability to functionally complement each other underscore their potential as targets for broad-spectrum antiviral therapies.